The impact of world crude oil price on the liberalisation of Malaysia’s paddy industry - Siti ‘Aisyah Baharudin, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Malaysia has adopted an open economy policy to boost its economic growth and per capita income. As a small and open economy, the country is susceptible to external shocks such as the 2008 financial crisis. Moreover, the increase in the international food price and the shortage of food in early 2008 imposed a new challenge to the national paddy sector. Besides, the increase in average world crude oil prices from USD 69.08 per barrel in 2007 to USD 101.56 per barrel in 2009 saw accompanied escalation in world food commodity prices, resulting in increases in input costs and hence the cost for food production. This paper examines the impact of the world crude oil price on the liberalisation of Malaysia’s paddy industry using system dynamics analysis. The two types of inputs impacted by crude oil price are fuel and fertiliser price. The results showed that 120 litre per hectare of diesel and petrol is the rate of fuel used in paddy production. The fertiliser consumption is 388.53 kilogram per hectare. The removal of fuel subsidies accompanied by the increase in the world crude oil prices significantly impacts farmers’ income and productivity levels as it triggers higher production expenses. The simulation results of the policy suggest that the subsidy rationalisation programme will free up more funds for product development such as precision farming technology as well as increased farm practices by farmers.